New species of Plectromacronema Ulmer 1906 (Trichoptera: Hydropsychidae) from Brazil, with association of immature stages and aspects of its biology. - Henrique Paprocki; Larissa Moreira-Silva (PLoS ONE)
Plectromacronema Ulmer 1906 is a Neotropical genus recorded sparsely from South of Mexico to the North of Argentina. The genus is placed within the Macronematinae sub-family, members of which are relatively large among the Trichoptera and bears conspicuous wing ornamentations. There are only two species recorded for Brazil, Plectromacronema comptum Ulmer 1906 and Plectromacronema subfuscum (Banks 1920). Plectromacronema lisae Flint 1983 recorded for Mexico and Costa Rica is the only species in the genus with immature stages described. Immature stages species level identification is required for water quality biomonitoring and most of the Trichoptera taxonomy is based only on adult male genitalia. In this paper, we propose a new species, Plectromacronema solaris sp.nov., larva, pupa, and adult. Aspects of the life history of the new species are also discussed. This record also represents a new genus record for the state of Minas Gerais, extending the knowledge on the diversity, distribution, biogeography, and biology of this remarkable genus.